Minocycline pre-treatment up-regulates antioxidant enzymes and enhances the regenerative potential of MSCs in rat myocardial infarction model - Omair Anwar; Mohiuddin; Irfan Khan; Asmat Salim (Journal of the Pakistan Medical Association, 2023)
Objective: To determine the effect of the pre-treatment of mesenchymal stem cells (MSCs) with minocycline on the expression of antioxidant genes and cardiac repair post myocardial infarction (MI) in rats. Methods: Rat bone marrow derived MSCs were used in the study. Cytotoxicity of minocycline in MSCs was determined using JC1 assay to identify a safe drug dose for further experiments. The MSCs were pre-treated with 1.0 µM minocycline for 24 hours and then treated with hydrogen peroxide (H2O2), after that mRNA was isolated and the expression levels of antioxidant genes including peroxiredoxin, glutathione peroxidase, and superoxide dismutase were determined. Finally, minocycline pre-treated MSCs were used to treat rats induced with MI by the ligation of left anterior descending coronary artery. The cardiac function was evaluated at two and four weeks post MI using echocardiography. Results: At 1.0 µM concentration, minocycline was found to be safe for MSCs and used for subsequent experiments. Minocycline pre-treatment was found to up regulate several antioxidant genes in oxidatively stressed MSCs. Furthermore, minocycline pre-treated MSCs displayed greater improvement in cardiac left ventricular function at two and four-weeks post MI as compared to untreated rats. Conclusions: Pre-treatment of MSCs with minocycline enhances the expression of antioxidant genes and promotes their capability to repair cardiac function after MI. Keywords: Antioxidants, Minocycline, Glutathione, Peroxiredoxins, Myocardial, Superoxide